Antibiotic resistance of Streptococcus pneumoniae in Vietnamese children with severe pneumonia: a cross-sectional study - Tran-Quang, Khai; Nguyen-Thi-Dieu, Thuy; Tran-Do, Hung; Pham-Hung, Van; Nguyen-Vu, Trung; Tran-Xuan, Bach; Larsson, Mattias; Duong-Quy, Sy (Frontiers in Public Health, 2023)
Background Streptococcus pneumoniae is the most common bacterium that causes community-acquired pneumonia (CAP) in children. The rate of S. pneumoniae resistance to antibiotics is increasing, particularly in patients with severe CAP. Therefore, the level of antibiotic resistance of S. pneumoniae causing severe CAP in Vietnamese children requires regular monitoring. Methods This was a cross-sectional descriptive study. Nasopharyngeal aspiration specimens from children were cultured, isolated, and examined for S. pneumoniae. Bacterial strains were assessed for antimicrobial susceptibility, and the minimum inhibitory concentration (MIC) was determined. Results Eighty-nine strains of S. pneumoniae were isolated from 239 children with severe CAP. The majority of isolates were completely non-susceptible to penicillin (1.1% intermediate, 98.9% resistant) and highly resistant to erythromycin (96.6%) and clarithromycin (88.8%); the rate of resistance to ceftriaxone was 16.9%, with the proportion of intermediate resistance at 46.0%; 100% of strains were susceptible to vancomycin and linezolid. For most antibiotics, MIC50 and MIC90 were equal to the resistance threshold according to the Clinical and Laboratory Standards Institute 2021; penicillin had an eight-fold increase in MIC90 (64 mg/L) and ceftriaxone had a 1.5-fold increase in MIC90 (6 mg/L). Conclusion Streptococcus pneumoniae isolates described in this study were resistant to many antibiotics. Penicillin should not be the first-line antibiotic of choice, and ceftriaxone at an enhanced dose should be used instead.